Gas exchange and yellow passion fruit production under irrigation strategies using brackish water and potassium - Wesley Alves Pinheiro, Francisco (Revista Ciência Agronômica, 2021)
The occ urrence of water sources with high concentrations of salts is a common problem in the semi-arid region of north-eastern Brazil. The search for management strategies that can minimize the effect of salt stress on crops is therefore extremely important. As such, this study aimed to evaluate gas exchange and production in the yellow passion fruit ‘BRS GA1’as a function of irrigation strategies using brackish water and doses of potassium. The research was carried out under fi eld conditions in São Domingos, in the state of Paraíba, Brazil, using a randomized block design in a 6 × 2 factorial scheme, with treatments comprising six irrigation strategies using water (irrigat ion with low-salinity water throughout the cycle – WS; irrigation with high-salinity water during the vegetative stage – VE; during the fl owering stage – FL; the fruiting stage – FR; during successive vegetative/fl owering stages - VE/FL; successive vegetative/fruiting stages - VE/FR) and two doses of potassium (60% and 100% of the recommended dose of 345 g K2O per plant per year), with four replications and three plants per plot. Two levels of water salinity (1.3 and 4.0 dS m-1) were used during different phenological stages of the crop. Irrigation with water at 4.0 dS m-1 reduced the leaf water potential, leaf osmotic potential, stomatal conductance, transpiration, and rate of CO2 assimilation of the yellow passion fruit, regardless of the irrigation strategy. The continuous salt stress during the vegetative and fl owering stages compromised production in the yellow passion fruit.